NaGdSi2O6 – A novel antiferromagnetically coupled silicate with Vierer chain structure - Kamutzki, Franz; Bekheet, Maged F.; Selve, Sören; Kampmann, Felix; Siemensmeyer, Konrad; Kober, Delf; Gillen, Roland; Wagner, Markus; Maultzsch, Janina; Gurlo, Aleksander; Hanaor, Dorian A.H. (Journal of Solid State Chemistry, 2023)
Ceramics based on pyroxenes and pyroxenoids present new pathways towards diverse functional materials. In this study, a novel sodium gadolinium pyroxene of the composition NaGdSi2O6 was successfully synthesised via a chelation-polymerization based sol-gel method and its crystal structure was determined by Rietveld refined synchrotron X-ray powder diffraction. NaGdSi2O6 crystallises in monoclinic symmetry with space group P21/c and unit cell parameters of a ​= ​5.44069(8) Å, b ​= ​13.83410(17) Å, c ​= ​7.66897(9) Å and β ​= ​109.9929(6)° (Z ​= ​4). The structure has been identified to be an inosilicate with a strongly undulated single tetrahedral chain along c with a chain periodicity of 4 (Vierer chain). Vierer chain-type NaGdSi2O6 shows a weak antiferromagnetic coupling, however there is no evidence for long-range magnetic order above 2 ​K.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Density functional theory; Pyroxenes; Pyroxenoids; Silicate ceramics; Vierer chain